2008
DOI: 10.1111/j.1442-200x.2007.02515.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection and interferon therapy in patients with Down syndrome

Abstract: IFN therapy for HCV infection in patients with DS may be unfavorable as compared with non-DS children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In addition, earlier studies have shown that two conditions were associated with nonresponsiveness to conventional interferon in pediatric patients; malignant disease and 21 trisomy [21,24]. This study shows that the therapy was similarly efficacious in pediatric and young adult patients with either of the two unfavorable factors as it was in those without them.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In addition, earlier studies have shown that two conditions were associated with nonresponsiveness to conventional interferon in pediatric patients; malignant disease and 21 trisomy [21,24]. This study shows that the therapy was similarly efficacious in pediatric and young adult patients with either of the two unfavorable factors as it was in those without them.…”
Section: Discussionsupporting
confidence: 48%
“…Pretreatment antinuclear antibodies or smooth muscle antibodies was negative and thyroid function was normal. Eighteen of the 37 patients, a part of these 18 patients having been reported previously, had failed to respond to monotherapy using natural interferon-a [20][21][22]. Institutional ethics committees at participating centers approved the protocols of the study.…”
Section: Methodsmentioning
confidence: 99%
“…In 2008, Miyoshi et al first reported the efficacy of natural IFN-a for HCV patients with DS. 1 Out of six study patients (five patients with genotype 1 and one with genotype 2) who received natural IFN-a, none had clearance of HCV-RNA in their serum. At that time, the Japan Society of Pediatric Hepatology did not encourage the exclusive use of natural IFN-a for the treatment of chronic HCV infection in patients with DS.…”
mentioning
confidence: 94%
“…At that time, the Japan Society of Pediatric Hepatology did not encourage the exclusive use of natural IFN-a for the treatment of chronic HCV infection in patients with DS. 1 In 2004, pegylated interferon (PEG-IFN)-a2a monotherapy for adult patients with chronic hepatitis C (CHC) was approved by the Japanese insurance system, following which PEG-IFN-a2b plus ribavirin (RBV) combination therapy was recommended in 2005. In 2012, the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition (NASPGHAN) created a pediatric HCV guideline working group, which first recommended that the duration of PEG-IFN/RBV combination therapy should be 48 weeks of treatment for genotypes 1 or 4 and 24 weeks for genotypes 2 or 3.…”
mentioning
confidence: 99%
“…However, the majority of these patients do not manifest clear clinical features of immunological disorders. Despite these observations, limited experiences with interferon-based therapy in the setting of Down syndrome showed dismal results with none of the patients responding to treatment [5], raising the question whether immunological disturbances in patients with Down syndrome may result in poor performance of immune-dependent interferon therapy [4]. …”
Section: Introductionmentioning
confidence: 99%